Optimization and simulation of a carbon-based flow-through composite anode configuration to enhance power generation and improve effluent quality simultaneously for microbial fuel cells. (20th August 2019) - Fu, Boya; Xu, Ting; Guo, Xingguo; Liang, Peng; Huang, Xia; Zhang, Xiaoyuan
Abstract: As a viable wastewater treatment and energy recovery technology, microbial fuel cell (MFC) requires more research with regard to the simultaneous achievement of high-quality effluent and high power generation. In this study, a novel flow-through carbon-based composite anode configuration is proposed, which combines the carbon cloth of two-dimensional anode with wooden granular activated carbon of three-dimensional anode. The proposed configuration enhances the performance of power production and chemical oxygen demand degradation by promoting the mass transfer, reducing internal resistance and increasing bioburden. Microbial fuel cell with the composite anode exhibited the highest maximum power density (1300 ± 50 mW m −2 ) and the highest chemical oxygen demand removal rate constant (0.155 ± 0.007 h −1 ) compared with the microbial fuel cell using the carbon cloth anode (1136 ± 46 mW m −2 and 0.072 ± 0.008 h −1 ) or the wooden granular activated carbon anode (1045 ± 32 mW m −2 and 0.129 ± 0.009 h −1 ). Meanwhile, at a lower chemical oxygen demand concentration (about 48 mg L −1 ), the microbial fuel cell with the composite anode maintained a current density of 2.4 A m −2, which is 18% higher than the wooden granular activated carbon anode (2.04 A m −2 ) and 400% higher than the carbon cloth anode (0.48 A m −2 ). The cyclic voltammetry and electrochemical impedance spectroscopy tests confirmed that the composite anodes displayed better electrochemical performance. Improving the flow rate and reducing the external resistance could effectively enhance the power production and chemical oxygen demand removal performance of microbial fuel cells, while the computational fluid dynamics simulation intuitively demonstrated the positive effect of the composite anode on chemical oxygen demand degradation. These results suggest that the flow-through composite anode provides a feasible strategy to simultaneously enhance the power generation and improve the effluent quality. Graphical abstract: Image 1 Highlights: A composite anode was constructed by optimizing 2D and 3D carbon anode materials. . Flow-through composite anode MFC had higher power generation and COD removal rate. Flow-through composite anode MFC maintained high power generation at low COD. Reducing external resistance and improving flow rate enhanced the MFC performance. Flow-through composite anode MFC was proved better COD removal in CFD simulation.